The Evolving Paleobathymetry of the Circum‐Antarctic Southern Ocean Since 34 Ma: A Key to Understanding Past Cryosphere‐Ocean Developments. (3rd August 2020) - Hochmuth, K.; Gohl, K.; Leitchenkov, G.; Sauermilch, I.; Whittaker, J. M.; Uenzelmann‐Neben, G.; Davy, B.; De Santis, L.
Abstract: The Southern Ocean is a key player in the climate, ocean, and atmospheric system. As the only direct connection between all three major oceans since the opening of the Southern Ocean gateways, the development of the Southern Ocean and its relationship with the Antarctic cryosphere has influenced the climate of the entire planet. Although the depths of the ocean floor have been recognized as an important factor in climate and paleoclimate models, appropriate paleobathymetric models including a detailed analysis of the sediment cover are not available. Here we utilize more than 40 years of seismic reflection data acquisition along the margins of Antarctica and its conjugate margins, along with multiple drilling campaigns by the International Ocean Discovery Program (IODP) and its predecessor programs. We combine and update the seismic stratigraphy across the regions of the Southern Ocean and calculate ocean‐wide paleobathymetry grids via a backstripping method. We present a suite of high‐resolution paleobathymetric grids from the Eocene‐Oligocene Boundary to modern times. The grids reveal the development of the Southern Ocean from isolated basins to an interconnected ocean affected by the onset and vigor of an Antarctic Circumpolar Current, as well as the glacial sedimentation and erosion of the Antarctic continent. The ocean‐wide comparison through time exposes patterns of ice sheet development such as switching of glacial outlets and the change from wet‐based to dry‐based ice sheets. Ocean currents and bottom‐water production interact with the sedimentation along the continental shelf and slope and profit from the opening of the ocean gateways. Plain Language Summary: The Southern Ocean is the only ocean which connects all three major world's oceans and therefore plays a vital role in our planet's oceanographic and atmospheric systems. We reconstruct the changing depth and geometry of the Southern Ocean seafloor since the establishment of a major ice sheet in Antarctica (34 Ma). We also provide an inventory of ice‐sheet eroded sediments deposited in the Southern Ocean, which has previously been highly underestimated. This ocean‐wide study shows the development of the Southern Ocean from individual, separated basins into the home of the strong Circumpolar current system, by the deepening of the land bridges between Antarctica and Australia and Antarctica and South America. The sediments deposited in the Southern Ocean, especially along the Antarctic margin, illustrate the growth and retreat of the Antarctic ice sheets showing two distinct pulses of enhanced sedimentation at the first continental‐scale glaciation of Antarctica (34 Ma) and after the warm phase of the Miocene Climatic Optimum. On a local and regional scale, we trace the amount of erosion provided by glacier systems along the Antarctic coast. The presented suite of seafloor grids will be made available to the geoscientific community and is an important additional input parameter for paleo‐models. Key Points: Suite of paleobathymetric grids encompassing key time intervals in Southern Ocean development since the Eocene/Oligocene Boundary Detailed sediment isopachs reveal two distinct sedimentation surges in relation to the advancement of the Antarctic Ice Sheets Reconstruction of the Southern Ocean gateways point to the potential of deep‐water exchange in the middle Oligocene